Plasmid characterization of Enterobacter sp. From human breast milk in Malaysia - Abd Samad, Fatin Illani (2015)
Enterobacter sp. species are nosocomial pathogens that could cause variety of infections, such as pneumonia, urinary tract infections or surgical wound infections. This ability in infecting human can cause by present of antibiotic-resistant plasmids which resistant toward antibiotics and this become a challenging clinical problem. The aim of this study is to isolate and characterize the plasmid extracted from Enterobacter cloacae from breast milk in Malaysian women. Extraction method of modified alkaline lysis and using Promega PureYield™ Plasmid Miniprep System were used to obtain high concentration of plasmids. The product size was expected to be ~11kbp and in this experiment, highly purified and concentrated plasmids were difficult to obtain thus, several modifications in plasmid extraction a required. PCR reaction was run using M13 universal primers and send for sequencing for the fragments which being amplify. This project was also being carried out to design a more versatile plasmid DNA which might aid in cloning system.